Development of a novel p72 gene-based loop-mediated isothermal amplification assay for the rapid detection of African swine fever virus in animal feed - Ge, Beilei; Domesle, Kelly J.; Simmons, Janine A.; Young, Shenia R.; Brake, David A.; McDonald, Ryan C.; Yancy, Haile F.; Gabbert, Lindsay R.; Neilan, John G.; Whitehouse, Chris A. (Frontiers in Veterinary Science, 2025)
IntroductionRapid and reliable detection of the African swine fever virus (ASFV), the causative agent of often fatal African swine fever, in animal feed is critical for implementing timely emergency control measures.MethodsWe developed a novel loop-mediated isothermal amplification (LAMP) assay targeting the ASFV p72 gene (B646L, encoding the major capsid protein) compatible with animal feed. Assay performance (referred to as LAMP1 in this study) was evaluated in comparison with a previously published topoisomerase II gene-based LAMP assay (LAMP2) and three p72 gene-based real-time PCR assays [two recommended by the World Organisation for Animal Health (WOAH) and the third one developed and currently used by the U.S. Department of Agriculture].ResultsLAMP1 was the fastest, with positive results obtained in as early as 3.8 min [compared to at least 5.5 min for LAMP2 and 20 cycles for real-time PCRs (~15 min)]. These assays could detect ASFV from 10−1 to 102 copies using synthetic DNA. LAMP1 detected as low as 101 TCID50/mL of ASFV BA71V stock and had a comparable performance to the USDA real-time PCR assay using both inclusivity (36 ASFV synthetic DNAs and isolates) and exclusivity (13 porcine viruses) panels. On applying six different DNA extraction methods to a variety of animal feed sample types (e.g., complete swine feed, soybean meal), variable yet mostly limited assay inhibitions were observed. When swine feed was inoculated with the ASFV BA71V stock at 105.1 TCID50/g, the newly developed LAMP1 assay reliably detected the virus within 7 min, in contrast to at least 20 min by the USDA real-time PCR (29 cycles).DiscussionFurther validation of this novel p72 gene-based LAMP assay in animal feed will pave the way for its adoption as a rapid screening tool in ASFV feed surveillance, as well as potential application in outbreak response and recovery efforts, to safeguard the nation’s animal feed supply.